Characteristics and correlation of gray matter volume and somatic symptoms in adolescent patients with depressive disorder - Mo, Daming; Guo, Pengfei; Hu, Shuwen; Tao, Rui; Zhong, Hui; Liu, Huanzhong (Frontiers in Psychiatry, 2023)
Background Adolescent patients with depressive disorders commonly exhibit somatic symptoms, which have a significant negative impact on their treatment and prognosis. Despite this, specific brain imaging characteristics of these symptoms have been poorly studied. Methods The Hamilton Depression Rating scale (HAMD-17), Children’s Functional Somatization scale (CSI), and Toronto Alexithymia scale (TAS) were used to evaluate the clinical symptoms of adolescent depression. We analyzed the correlation between brain gray matter volume (GMV) and clinical symptoms in adolescent patients with depression and somatic symptoms. Results The depression subgroups with and without functional somatic symptoms (FSS) had higher scores on the HAMD-17, CSI, and TAS than the normal control group. The group with FSS had higher HAMD-17, CSI, and TAS scores than the depression group without FSS (p < 0.05). CSI and TAS scores were positively correlated (r = 0.378, p < 0.05). The GMV of the right supplementary motor area was higher in the depression groups with and without FSSs than in the normal control group, and the GMV was higher in the group without FSS than in the group with FSS (F = 29.394, p < 0.05). The GMV of the right supplementary motor area was negatively correlated with CSI in the depressed group with FSS (r = −0.376, p < 0.05). In the group with depression exhibiting FSS, CSI scores were positively correlated with GMV of the middle occipital gyrus (pr = 0.665, p = 0.0001), and TAS scores were positively correlated with GMV of the caudate nucleus (pr = 0.551, p = 0.001). Conclusion Somatic symptoms of adolescent depressive disorder are associated with alexithymia; moreover, somatic symptoms and alexithymia in adolescent patients with depressive disorders are correlated with GMV changes in different brain regions.